2015
DOI: 10.1007/s00418-015-1351-1
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial electrical resistance (TEER): a functional parameter to monitor the quality of oviduct epithelial cells cultured on filter supports

Abstract: Cultivation of oviduct epithelial cells on porous filters fosters in vivo-like morphology and functionality. However, due to the optical properties of the filter materials and the cells’ columnar shape, cell quality is hard to assess via light microscopy. In this study, we aim to evaluate transepithelial electrical resistance (TEER) measurement as a prognostic quality indicator for the cultivation of porcine oviduct epithelial cells (POEC). POEC were maintained in four different types of media for 3 and 6 w to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 26 publications
3
93
0
3
Order By: Relevance
“…Mgf was analysed in both the A and B compartments to calculate the value of Papp (Figure 11). The TEER values were continuously recorded while performing experiment, showing miniscule reduction (i.e., <10%) in TEER value on the treated cells wrt the control cells which indicated that there was slight opening of the tight junctions of Caco-2 cells, signifying paracellular transport (Sha et al, 2005;Chen et al, 2015;Laksitorini et al, 2015).…”
Section: Bidirectional Permeability Assaymentioning
confidence: 99%
“…Mgf was analysed in both the A and B compartments to calculate the value of Papp (Figure 11). The TEER values were continuously recorded while performing experiment, showing miniscule reduction (i.e., <10%) in TEER value on the treated cells wrt the control cells which indicated that there was slight opening of the tight junctions of Caco-2 cells, signifying paracellular transport (Sha et al, 2005;Chen et al, 2015;Laksitorini et al, 2015).…”
Section: Bidirectional Permeability Assaymentioning
confidence: 99%
“…Trans‐epithelial electrical resistance (TEER) measurements are widely used in biology and tissue engineering to determine epithelial and endothelial cell health and membrane integrity. These measurements give an indirect, noninvasive assessment of the permeability of cellular tight junctions and ultimately the barrier function of a cellular monolayer or 3D tissues (Chen, Einspanier, & Schoen, 2015; Schmitz et al, 2018). There are several variables known to affect the final readout including electrode size, measurement temperature, media formulation, time in culture, and cell passage number, making it difficult to standardize measurements (Elbrecht, Long, & Hickman, 2018; Srinivasan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Trans-epithelial electrical resistance (TEER) measurements are widely used in biology and tissue engineering to determine epithelial and endothelial cell health and membrane integrity. These measurements give an indirect, noninvasive assessment of the permeability of cellular tight junctions and ultimately the barrier function of a cellular monolayer or 3D tissues (Chen, Einspanier, & Schoen, 2015;Schmitz et al, 2018).…”
mentioning
confidence: 99%
“…Several methods exist to assess endothelial/epithelial cell monolayer confluence and barrier quality, including determination of fluid filtration coefficient (K f ), hydraulic conductivity (L p ), apparent solute permeability (P app ), and transepithelial electrical resistance (TEER) [40,41]. In our work, we have selected to measure the apparent solute permeability (P app ) through a drug transport assay, as it is the most direct measurement for evaluating our variable of interest: the permeability of the Caco-2 monolayer to paracellularly transported drugs [42].…”
Section: Introductionmentioning
confidence: 99%